5-HT2A and 5-HT3 receptors contribute to the exacerbation of targeted and non-targeted effects of ionizing radiation-induced cell death in human colon carcinoma cells. (2nd April 2020) - Curtis, Jacob J.; Vo, Nguyen T. K.; Seymour, Colin B.; Mothersill, Carmel E.
Abstract: Purpose: Serotonin (5-HT) is implicated in the underlying mechanisms which mediate cell death following ionizing radiation exposure, however, effects appear to be cell type-dependent. We sought to further characterize the role of 5-HT and 5-HT receptors (5-HTRs) in the exacerbation of cell death following ionizing radiation exposure in human colon carcinoma cells. Materials and methods: We examined the clonogenic survival of colon carcinoma HCT116 cells treated with 5-HT and the selective 5-HTR antagonists ketanserin (5-HT2A ) and ondansetron (5-HT3 ), following exposure to direct ionizing radiation and irradiated cell-conditioned medium (ICCM). The relative expression of these target receptors was measured using western blotting. Results: Western blotting results revealed that relative protein levels of the 5-HT2A and 5-HT3 receptors were similar. 5-HT concentration-dependent increases in cell death that occurred following direct ionizing radiation exposure were abolished by both 5-HTR antagonists. Death of nonirradiated cells recipient of ICCM was increased in a concentration-dependent manner by 5-HT when present during donor cell irradiation. Both 5-HTR antagonists completely abolished the increases in bystander-induced cell death generated by 5-HT. Finally, we show that exposure of cells to 5-HT prior to receipt of ICCM can also dictate the degree of bystander-induced cell death. Conclusions: Our findings demonstrate a definitive role for 5-HT in the exacerbation of cell death following ionizing radiation exposure in colon carcinoma cells and highlight 5-HTRs as potential markers for predicting cellular radiosensitivity.